An in vitro Perfused Macroencapsulation Device to Study Hemocompatibility and Survival of Islet-Like Cell Clusters - Fernandez, Stephanie A.; Danielczak, Lisa; Gauvin-Rossignol, Gabrielle; Hasilo, Craig; Bégin-Drolet, André; Ruel, Jean; Paraskevas, Steven; Leask, Richard L.; Hoesli, Corinne A. (Frontiers in Bioengineering and Biotechnology, 2021)
Transplantation of hydrogel-encapsulated pancreatic islets is a promising long-term treatment for type 1 diabetes that restores blood glucose regulation while providing graft immunoprotection. Most human-scale islet encapsulation devices that rely solely on diffusion fail to provide sufficient surface area to meet islet oxygen demands. Perfused macroencapsulation devices use blood flow to mitigate oxygen limitations but increase the complexity of blood-device interactions. Here we describe a human-scale in vitro perfusion system to study hemocompatibility and performance of islet-like cell clusters (ILCs) in alginate hydrogel. A cylindrical perfusion device was designed for multi-day culture without leakage, contamination, or flow occlusion. Rat blood perfusion was assessed for prothrombin time and international normalized ratio and demonstrated no significant change in clotting time. Ex vivo perfusion performed with rats showed patency of the device for over 100 minutes using Doppler ultrasound imaging. PET-CT imaging of the device successfully visualized metabolically active mouse insulinoma 6 ILCs. ILCs cultured for 7 days under static conditions exhibited abnormal morphology and increased activated caspase-3 staining when compared with the perfused device. These findings reinforce the need for convective transport in macroencapsulation strategies and offer a robust and versatile in vitro system to better inform preclinical design.